2020
DOI: 10.1080/0951192x.2020.1775301
|View full text |Cite
|
Sign up to set email alerts
|

Agile product development process transformation to support advanced one-of-a-kind manufacturing

Abstract: Increased competition in the global market has forced companies to diversify their product ranges to meet the customers' changing needs and adopt product development strategies for mass customization or even one-of-a-kind production, which inevitably requires designing modular products. Product modularity is achieved via platform-based systems, in which various combinations of different modules are assembled within a common platform. The smart factories that are already beginning to appear to employ a complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Such challenges and external threats can also encompass the adoption of new systems and technologies [9]. The agile process offers one such solution through customer-focused product development [10]. Despite software development being the initial idea of agile methods, crowdsourcing and the internet of things provide new opportunities for development [11].…”
Section: Introductionmentioning
confidence: 99%
“…Such challenges and external threats can also encompass the adoption of new systems and technologies [9]. The agile process offers one such solution through customer-focused product development [10]. Despite software development being the initial idea of agile methods, crowdsourcing and the internet of things provide new opportunities for development [11].…”
Section: Introductionmentioning
confidence: 99%
“…They found that agile manufacturing model has better performance outcomes in comparison with others. Agile manufacturing has emerged as a new approach to planning and conducting manufacturing activities by efficiently connecting the available resources (Varl et al, 2020). Butcher (2007) mentioned that RFID implementation improves supply chain agility and helps in minimizing inventory holding leading to better stock management and reduced error in product data handling.…”
Section: Literature Review 21 Contribution Of Agile Manufacturing In ...mentioning
confidence: 99%
“…Technology has evolved as the most critical success factor of the agile manufacturing implementation (Dubey and Gunasekaran, 2015). Seamless data Agile manufacturing practices and business communication well supported by software and hardware is the key to success in gearing up the business to keep pace with accelerating environmental dynamics and meet customer demands (Vazquez-Bustelo et al, 2007;Varl et al, 2020). Speed is the by-product of flexible organizational structure and up-to-date technology acquisition (Van Assen et al, 2000;Khatri et al, 2016).…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining APM and concurrent product development elements has also been recognized as a promising solution for advanced mass customization and one-of-a-kind production [52]. The study of Varl et al showed that such a combination can result in great direct savings (reduced time to market, rework, man-hours, etc.)…”
Section: Hybrid Modelsmentioning
confidence: 99%